Diagnostik und Therapie von Harnröhrenstrikturen – Leitlinienübersicht 2024 : Teil 1 – anteriore Harnröhre - Klemm, Jakob; Dahlem, Roland; Kluth, Luis A; Rosenbaum, Clemens M; Shariat, Shahrokh F; Fisch, Margit; Vetterlein, Malte W; Trauma and Reconstructive Urology Working Party of the European Association of Urology Young Academic Urologists (Urologie (Heidelberg, Germany), 2024)
In recent years, several international urological societies have published guidelines on the diagnosis, treatment, and follow-up of urethral strictures, but a guideline for the German-speaking region has not been available to date. This summary provides a detailed comparison of the guidelines of the European Association of Urology (EAU), American Urological Association (AUA) and the Société Internationale d'Urologie (SIU) with regard to the treatment of anterior urethral strictures, i.e. from the bulbar urethra to the meatus. In the following work, differences and specific recommendations in the guidelines are highlighted. In particular, the three guidelines largely agree with regard to diagnostic workup and follow-up. However, divergences exist in the management of anterior urethral strictures, particularly with regard to the use of endoscopic therapeutic approaches and the use of urethral stents. In addition, the EAU provides more comprehensive and detailed recommendations on urethroplasty techniques and specific patient follow-up. The EAU guidelines are the most current and were the first to include instructions for urethral strictures in women and individuals with gender incongruence after genital approximation surgery. Reconstructive urology is a rapidly evolving specialty and, thus, the clinical approach has been changing accordingly. Although guideline recommendations have become more inclusive and comprehensive, more high-quality data are needed to further improve the level of evidence.
Keywords: Spojené státy americké; Humans; Evidence-based medicine; Data Accuracy; Female; správnost dat; lidé; uretra; Plastic Surgery Procedures; Endoscopy; United States; Urethroplasty; Urethra; ženské pohlaví; zákroky plastické chirurgie; Urethral Stricture; striktura uretry; urologie; Patient-reported outcome measures; Urology; Hypospadias